DAMPAK JUDI ONLINE SLOT TERHADAP KEHARMONISAN KELUARGA DI KOTA PEKANBARU - Rahman, Alwi (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
This study aims to examine the impact of online slot gambling on family harmony in Pekanbaru City. Online gambling is increasing among Indonesian people, including in Pekanbaru, and has negative effects both economically, psychologically, and socially for the perpetrators and their families. This study uses a qualitative approach with an in-depth interview method with several informants with different professions and social backgrounds, including workers in government agencies, modern markets, small entrepreneurs, and private workers. The main focus of this research is to identify the driving factors of involvement in online gambling, as well as to see how changes in the behavior of gambling players affect the dynamics and harmony in their families. The results show that environmental influences and economic factors are the main triggers for someone to get involved in Online Slot gambling. In addition, the behavior of online gambling players causes family disharmony, which can be seen from household conflicts, decreased communication quality, and emotional instability. The findings also show that although some players attempt to quit, the temptation to return to gambling remains, creating a pattern of addiction that is difficult to break. Therefore, government interventions as well as community and family support are needed to help gambling players quit and prevent further adverse impacts.